Radiological finding in pediatric patients with urinary tract infections - Al-naddawi, Mahjoob N.; Rida, Muneera F. (Journal of the Faculty of Medicine Baghdad, 2011)
Background; determining what radiologic studies to obtain following the diagnosis of a urinary tract infection(uti) is an area of medicine that is still not agreed upon, nor is there a gold standard. Objective; to study the radiological abnormalities in paediatric patients with urinary tract infections. Patients and methods; this prospective study was done from the first of june 2008 to the first of may 2009 include 104 pediatric patients who were referred to children welfare hospital ,(pediatric nephrological out patient clinic) with signs and symptoms of urinary tract infections, all of them had culture positive urine examination , ultrasonograhy was done for all patients, voiding cystouretherography was done for patients with recurrent attacks of urinary tracts infections (58 patients),and intravenous urography was done for patients with urinary tract abnormalities on ultrasonography (41patients). Results; the results of the present study showed that about 63( 59.4%)of infants and children with (culture positive) urinary tract infections had positive ultrasonic findings ,the most frequent ultrasonic findings was pelvicalyceal and ureteral dilatation whichwas observed in 32.6%. Thirty four(32.6% )of patients had positive findings on voiding cystography ,( grade 5&4 reflux found in 22.4%). The intravenous urography study was beneficial in diagnosis of pelviureteric junction obstruction in 12.2% and visualized the obstructive effect of renal and ureteric stones in 24.4%. Conclusion; the positive radiological findings supported the idea that the patients with recurent urinary tract infections need imaging work up.